Development of Pop-up Book Media Based on Scientific Literacy for Class V SD Muhammadiyah 1 Kisaran - Antin Faridha; Ashar Hasairin; Wildansyah Lubis (RIRAI Publisher, 2023)
This study aims to determine the validity, practicality, and effectiveness of pop-up books in science lessons on the food digestive system. This type of research is the ADDIE (Analyze, Design, Development, Implementation and Evaluation) model development research. Data collection techniques in this study are observation, interviews, validation and tests. This research was conducted in class V. The results showed 1) Valid products in terms of material were 95%, media 96%, scientific literacy 92%, language 91%; 2) The product received a positive response from students with a percentage of 83%; and the proportion of classical completeness reaches 85% or most of the student learning outcomes are declared complete.